How Economic Diplomacy Shapes Export Performance: Theoretical Perspectives and Future Directions - Najm Abdullah Mohsen Al-Saad, Yasmine (Iraqi Journal for Administrative Sciences, 2026)
The current study aims to develop a conceptual framework to explore the role of economic diplomacy in export promotion. By integrating four theoretical frameworks—institutional theory, resource theory, network theory, and transaction cost economics—the study adopts a conceptual and theoretical research approach. The paper highlights four key mechanisms through which economic diplomacy influences export outcomes: institutional legitimacy, resource provision, network integration, and transaction cost reduction. It also points to contextual conditions that may affect the quality of economic diplomacy, including institutional quality and the alignment of diplomatic initiatives with domestic policies. Formal proposals (P1–P6) are presented to clarify these theoretical links and guide future field research. The paper draws lessons relevant to the Iraqi context and demonstrates how diplomatic strategies can enhance institutional credibility, support local businesses, and reduce risks associated with international trade. By integrating multiple theoretical perspectives and drawing policy-relevant insights, this study contributes to the literature on international business and international economics, providing a basis for empirical testing and useful recommendations for policymakers for policymakers aiming to strengthen export performance through the use of economic diplomacy tools.